Herança da resistência do feijoeiro à raça 73 de Colletotrichum lindemuthianum - JUNIOR, TRAZILBO JOSE DE PAULA; BAÍA, GILSON SOARES; ALZETE-MARIN, ANA LILIA; BARROS, EVERALDO GONÇALVES DE; MOREIRA, MAURILIO ALVES (Revista Ceres, 2015)
.